PEMAHAMAN KONSEP MATERI PERKULIAHAN MELALUI KUIS DENGAN APLIKASI GOOGLE FORMS PADA MATA KULIAH BUDAYA MELAYU DI FKIP UNIVERSITAS RIAU - Achmad, Said Suhil; Natuna, Daeng Ayub (STKIP Pesisir Selatan, 2021)
This study aims to describe 1) the ability to write in their own language; 2) The ability to make fragments that show a certain meaning of the material; 3) Ability to assemble material based on the sequence of processes; 4) the ability to write an idea clearly; 5) Ability to make material conclusions; 6) The ability to be able to find the main idea in the material; and (7) The ability to retell in their own language. The study used a descriptive quantitative approach, taking a sample of 40 people using an online questionnaire. The questionnaire has been declared valid and reliable through a trial on 15 students outside the study. Data processing using descriptive statistics. The results of this study found that the majority of students during lectures were outside the city of Pekanbaru, the device used was Android, the network used was data packets, while their internet network was always in moderate condition, but student learning achievement (GPA) was above average, so that it can allow students during lectures to understand the concept of material through online quizzes using google forms. It was found that almost all students could understand the concept of material through online quizzes using google forms, especially on the ability to write in their own language, and the ability to retell in their own language. This is possible because students' abilities are above average even though the internet network they use is weak